2015
DOI: 10.1007/s00127-015-1071-9
|View full text |Cite
|
Sign up to set email alerts
|

Is the prevalence of ADHD in Turkish elementary school children really high?

Abstract: Our results confirmed a substantially higher ADHD prevalence rate (more than double) than the suggested pooled worldwide prevalence, although similar to the one recently detected in a representative populational sample of children in the US (11 %). These findings, consistent with previous developmental epidemiology studies from Turkey, confirm that ADHD is highly prevalent in Turkish elementary school children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 38 publications
4
25
1
3
Order By: Relevance
“…31 Although no similar studies have been reported from the TRNC to date, our methodology and results are in close agreement with studies of Turkish children from Turkey, such as the epidemiological study reported by Ercan et al 30 from the İzmir province of Turkey, which used a very similar method-logy and reported a prevalence of 13.6%. Two other epidemiological studies, one by Ercan et al 21 another by Rowland et al 9 reported highly similar results to ours, 12.7% and 12.9% respecttively. In Chilean children aged 4-18 years the prevalence of ADHD was found to be 10.4%.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…31 Although no similar studies have been reported from the TRNC to date, our methodology and results are in close agreement with studies of Turkish children from Turkey, such as the epidemiological study reported by Ercan et al 30 from the İzmir province of Turkey, which used a very similar method-logy and reported a prevalence of 13.6%. Two other epidemiological studies, one by Ercan et al 21 another by Rowland et al 9 reported highly similar results to ours, 12.7% and 12.9% respecttively. In Chilean children aged 4-18 years the prevalence of ADHD was found to be 10.4%.…”
Section: Discussionsupporting
confidence: 88%
“…We found that the percentage of children meeting ADHD diagnostic criteria was 12.8%. Although this rate is markedly higher than the 5.9% reported by a worldwide meta-analysis of ADHD prevalence, 14 it is within the range that has been reported for ADHD prevalence 9 as well as that of epidemiological studies conducted in Turkey, 21,30 and Chile. 31 Although no similar studies have been reported from the TRNC to date, our methodology and results are in close agreement with studies of Turkish children from Turkey, such as the epidemiological study reported by Ercan et al 30 from the İzmir province of Turkey, which used a very similar method-logy and reported a prevalence of 13.6%.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…The prevalence of ADHD in Diagnostic and Statistical Manual of Mental Disorders (DSM-5) was reported to be 5% in children and adolescents (8). The prevalence of ADHD in our country was found to be 8.1% in a study conducted in 2004, 12.7% in a study conducted in 2014 and 12.4% in a study conducted in 2018 (6,9,10). The changes in diagnostic criteria and public awareness works have played an important role in increasing the incidence of ADHD in recent years.…”
Section: Introductionmentioning
confidence: 72%